Belgische Abstracten 1948-1968. - Meskens, Emiel; Bank Brussel Lambert, Gent (Gent : Bank Brussel Lambert, 1991)
Van Anderlecht, Englebert ; Anthoons, Willy ; Bertrand, Gaston ; Beullens, André ; Bogaert, André ; Bogart, Bram ; Bonnet, Ann ; Van Breedam, Camiel ; Burssens, Jean ; Bury, Pol ; Collignon, Georges ; Cortier, Amédée ; Van Damme, Suzanne ; Decock, Gilbert ; Delahaut, Jo ; Van Doorslaer, Etienne (Maur-Etienne) ; Drybergh, Charles ; Gentils, Vic ; Guiette, René ; Van Hoeydonck, Paul ; Holmens, Gerard ; De Keyser, Raoul ; Lacasse, Joseph ; Leblanc, Walter ; de Leeuw, Bert ; Lewy, Kurt ; Van Lint, Louis ; Mara, Pol ; Mendelson, Marc ; Milo, Jean ; Mortier, Antoine ; Peire, Luc ; Plomteux, Léopold ; Raveel, Roger ; Rets, Jean ; Saverys, Jan ; Van Severen, Dan ; Van Sumere, Hilde ; Vandenbranden, Guy ; Vandercam, Serge ; Vercammen, Wout ; Verheyen, Jef ; Verstockt, Mark ; Vonck, Fernand (Ferdinand) ; Wyckaert, Maurice
Nederlands
Belgische Abstracten 1948 - 1968, BBL (Bank Brussel Lambert) Gent / Magnus Fine Arts Gent, 03.1991
boek
Keywords: jaren 50; jaren 60; België